Guava Fruit Fly, Anastrepha striata Schiner (Insecta: Diptera: Tephritidae) - Howard V. Weems, Jr.; Thomas R. Fasulo (EDIS)
Anastrepha striata Schiner is one of the most common species of fruit flies throughout most of its range. It, however, has not acquired a well established common name as have others such as the Mexican, Caribbean, and Mediterranean fruit fly. This probably is because it is not considered to be of primary economic importance, although it often is abundant and may be highly destructive to dooryard plantings of some tropical fruits. This document is EENY-265 (originally published as DPI Entomology Circular 245), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: January 2002.